Effectiveness of an Educational Program on Oncology Nurses Knowledge about Diagnostic Bone Marrow Aspiration and Biopsy at Blood Diseases Center in Medical City Directorate - Abbas Labeeb Wadi Al-Gbury, Khalida M. Khudur, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Bone marrow aspiration and biopsy is a procedure which done for patients may be have a blood disorder or a suspected or previously diagnosed blood malignancy. Bone marrow examination is done during the initial diagnosis and/or staging and used to determine treatment response in patients with leukemia, lymphoma, and other blood disorders. Aims: To evaluate the effect of an educational program on nurse’s knowledge related to about Diagnostic Bone Marrow Aspiration and Biopsy at blood diseases center in medical city directorate. Methodology: A pre experimental study design (one group Pretest-Posttest study design) on 20 nurses who work in bone marrow examination unit, it is carried out through the application of pre-test and post-test approach for the study group, from the period 13th June to 13th of December 2021. Three sessions were submitted to the nurses that participate in an educational program. Results: The results of current study indicated that that there were significances differences between pre and post educational program related to nurses knowledge. Conclusion: Based on the study findings that the program applied has an observational enhanced nurses’ knowledge relating to the bone marrow aspiration and biopsy management.